A Low-Cost Modified Energy Detection-Based Spectrum Sensing Algorithm with GNU Radio for Cognitive Radio - Baker, Delores; Beal, Aubrey N.; Joiner, Laurie; Syed, Tamseel M. (Proceedings of IEEE Southeastcon, 2023)
Spectral efficiency persists as an issue with the increasing demand for interconnectivity and applications involving IoT. In this work, we present a low cost, modified energy detection algorithm to perform spectrum sensing for possible use in space constrained and energy limited applications. Modifications are made to the theoretical energy detection algorithm and then implemented in GNU Radio utilizing a more economical commercial-off-the-shelf SDR. The proposed algorithm eliminates the need for an exclusive FFT block as part of the RX chain in GNU Radio and works without requiring a large sample rate. The spectrum sensing results presented demonstrate and validate energy detection methods using this low-cost, accessible experiment.